Acculturation and Adaptation of Syrian Refugees in Turkey: The role of (dis)concordance of acculturation orientations and identity threat - Terzi, I.; Guerra, R.; Bierwiaczonek, K. (Examining complex intergroup relations: Through the lens of Turkey, 2022)
The present chapter examined the social-psychological factors associated with the adaptation of Syrian refugees in Turkey. Specifically, building on the mutuality approach to acculturation, the current research considered both the role of refugees’ acculturation orientations towards culture maintenance and contact with the Turkish society, refugees’ meta-perceived acculturation orientations of the Turkish host society and the impact of perceived (dis)concordance of acculturation orientations and perceived identity threat (i.e., discrimination) on their psychological and sociocultural adaptation. This research extends previous research conducted with Syrian refugees in Turkey by examining both psychological and sociocultural adaptation of refugees and by considering the specific impact of (dis)concordance of acculturation orientations. Using data from a survey (109 participants) the results showed a negative association between own culture maintenance and psychological adaptation, whereas own desire for contact was not associated with sociocultural adaptation. Extending previous research, refugees’ perceived acculturation orientations from Turkish society, particularly perceived desire for contact, were positively related to psychological and sociocultural adaptation (albeit marginally for the latter). Finally, perceived discordance of acculturation was negatively related to psychological and sociocultural adaptation and positively related to perceived discrimination. The theoretical and practical implications of these results are discussed.